Al2O3:C optically stimulated luminescence droplets: Characterization and applications in medical beams. (November 2016) - de F Nascimento, Luana; Vanhavere, Filip; Souza, Rodolfo; Verellen, Dirk
Abstract: Optically stimulated luminescence (OSL) detectors, which are widely used in radiation protection, offer a number of potential advantages for radiotherapy dosimetry. In this study we characterized 1-μl of OSL droplets consisting of a mixture of Al2 O3 :C powder and a photo-curable polymer, in addition to results described in a previous work (Nascimento et al., 2013). The concentration test showed that droplets have a higher spatial resolution than other commonly used Al2 O3 :C-based detectors. Our results from the dose response, reproducibility and dependence with accumulative dose were obtained for droplets with a powder/polymer concentration that showed a high Signal to Noise Ratio (SNR) without compromising the droplet malleability. Additional test results show the response of such droplets in percentage depth dose curves and dose profiles of clinical beams. Highlights: Droplets composed of thin powder of Al2 O3 :C were prepared using a photo-curable polymer. Droplets present high spatial resolution. The droplets were characterized in calibration sources to be used as 1D. The droplets were exposed to different medical beams.